التحول نحو الصيرفة الالكترونية كآلية لتفعيل التجارة الالكترونية في الجزائر - مصداع, راضية; بودبودة, زهرة (جامعة الوادي - University of Eloued, 2021)
أكدت التطورات المالية والمصرفية على الصعيد العالمي أهمية سلامة الجهاز المصرفي ومدى تطوره، باعتباره عنصرا حيويا يؤدي دورا رياديا واستراتيجيا في تنفيذ أهداف السياسة الاقتصادية للدولة بعنصريها المالي والنقدي، لهذا فقد بادرت الدولة الجزائرية إلى إصلاح المنظومة المصرفية بهدف تحديث وعصرنة البنوك الجزائرية لمواكبة التحديات التي يفرضها عصر التجارة الالكترونية، وتهدف هذه الدراسة إلى إبراز واقع تبني البنوك التجارية الجزائرية لدعائم إرساء الصيرفة الالكترونية كآلية جديدة تعتمد عليها في تنشيط المبادلات التجارية على المستوى المحلي أو الدولي، خاصة في ظل انتشار وسرعة نمو التجارة الالكترونية. وقد توصلت الدراسة إلى أن البنوك الجزائرية عرفت تطور ملحوظ خلال السنوات الأخيرة في مجال تحسين مستوى جودة الخدمات المصرفية التي تقدمها، ولكنها لا تزال تعاني النقص في استخدام التكنولوجيا المصرفية في إطار التحول نحو الصيرفة الالكترونية وذلك لتأخر الجزائر في تطبيق واعتماد التجارة الالكترونية. Financial and Banking developments at the international level have emphasized the importance of the safety of the banking system and its extent of development, as it is a vital element that plays a leading and strategic role in implementing the goals of the economic policy ofthe state with its financial and monetary aspects. For this reason, the Algerian state has embarked on reforming the banking system with the aim of modernizing and modernizing Algerian banks to cope with the challenges posed by the era of electronic commerce. International, especially in light of the proliferation and rapid growth of electronic commerce. The study concluded that Algerian banks have experienced significant development in recent years in the field of improving the quality of the banking services they provide. However, they are still suffering from a shortage in the use of banking technology in the context of a shift towards electronic banking.
Transition to electronic Banking as a mechnism to activate electronic commerce in Algeria
مقال
Keywords: التجارة الالكترونية ; الصيرفة الالكترونية ; البنوك الالكترونية; e-banking ; E-commerce